IgG4-related disease involving vital organs diagnosed with lip biopsy: A case report and literature review. Issue 24 (June 2016) - Akiyama, Mitsuhiro; Kaneko, Yuko; Hayashi, Yutaro; Takeuchi, Tsutomu
Abstract : Abstract: Immunoglobulin G4-related disease (IgG4-RD) is a recently recognized new disease entity characterized by elevated serum IgG4 and infiltration of IgG4 + plasma cells in affected tissues. Histological examination is essential for definitive diagnosis, as other pathological conditions can also present with serum IgG4 elevation. However, IgG4-RD frequently involves vital or internal organs that are difficult to perform biopsies. We herein report a unique case of IgG4-RD involving vital organs that could be successfully diagnosed by alternative lip biopsy, an accessible, little invasive procedure, despite no apparent manifestation demonstrating the involvement in labial salivary gland. A 60-year-old man with swelling of both submandibular glands and elevated serum creatinine level visited our hospital. His labial salivary glands appeared normal. His blood test showed high serum IgG4, and positron-emission computed tomography revealed abnormal uptake in submandibular glands, periaorta, and left kidney with hydronephrosis. We suspected him of IgG4-RD; however, the involved organs were difficult to approach for histological examination. Alternatively, we performed lip biopsy and proved massive infiltration of IgG4 + plasma cells leading to the diagnosis with IgG4-RD. Treatment with prednisolone resulted in the remarkable improvement of organ involvements and the normalization of serum IgG4 level after 3 months. Prednisolone was gradually tapered without the relapse of disease. The early recognition and diagnosis of IgG4-RD is clinically important because delay in the treatment initiation leads to fibrosis with irreversible organ damage. Our case highlights the possibility that lip biopsy is a promising option for histological examination in patients with IgG4-RD in whom affected organs are difficult to access, leading to early diagnosis with appropriate treatment.